Congenital Syphilis Prevention: Strategies, Evidence, and Future Directions. (September 2018) - Plotzker, Rosalyn E.; Murphy, Ryan D.; Stoltey, Juliet E.
Abstract : Background: Congenital syphilis (CS)—the preventable transmission of Treponema pallidum from infected mother to fetus—remains a significant problem worldwide. Methods: From July through November 2017, 239 articles relevant to CS prevention were identified via keyword searches in PubMed and Google Scholar, ancestry searches, and expert recommendation. Articles were then assessed for (1) measurement of a specified CS or adverse pregnancy outcomes (APOs) and (2) geographic setting in high/upper middle income countries according to United Nations criteria. In total, 119 articles met inclusion criteria. These were then vetted for 1 of 3 arms of CS prevention, after which additional ancestral searches were conducted within each arm to arrive at the final collection of articles per CS prevention strategy—maternal prenatal treatment (n = 33), prenatal screening (n = 24), and public health interventions that support screening and treatment (n = 15). Results: Of the 7 studies that evaluated treatment with benzathine penicillin G (BPG) use within the context of a modern health care system, all showed BPG to be highly effective in CS prevention; 3 additional studies demonstrated BPG effectiveness in preventing APOs. Ten studies revealed early disease detection through prenatal screening significantly reduces CS and APOs when paired with BPG. There was limited literature evaluating public health interventions, such as partner notification, surveillance, and prenatal screening laws. Conclusions: Congenital syphilis is a preventable disease, effectively avoided with appropriate prenatal screening and BPG therapy. Increasing syphilis rates among all adults, accompanied by gaps in the provision of prenatal care to women at high risk of infection, are major contributors to CS persistence.